Infodemic: a blessing or curse? - Sivakumar, Abinav; Boratne, Abhijit V. (International Journal Of Community Medicine And Public Health, 2022)
Due to the speed and scale of the transmission of the disease, coronavirus disease 2019 (COVID-19) was declared pandemic by the WHO on 11 March 2020 mainly. We’re not just fighting an epidemic; we’re fighting an infodemic, said WHO director-general Tedros Adhanom Ghebreyesus at the Munich security conference. WHO stated infodemic as an overabundance of information some accurate and some not that makes it hard for people to find trustworthy sources and reliable guidance when they need it. It can lead to confusion and ultimately mistrust in governments and public health response. The systematic use of risk- and evidence-based analysis and approaches to manage the infodemic and reduce its impact on health behaviours during health emergencies, was said to be as infodemic managenent.